Understanding the role of AMPA receptors in autism: insights from circuit and synapse dysfunction - Jimenez-Gomez, Andres; Nguyen, Megan X.; Gill, Jason S. (Frontiers in Psychiatry, 2024)
Autism spectrum disorders represent a diverse etiological spectrum that converge on a syndrome characterized by discrepant deficits in developmental domains often highlighted by concerns in socialization, sensory integration, and autonomic functioning. Importantly, the incidence and prevalence of autism spectrum disorders have seen sharp increases since the syndrome was first described in the 1940s. The wide etiologic spectrum and rising number of individuals being diagnosed with the condition lend urgency to capturing a more nuanced understanding of the pathogenic mechanisms underlying the autism spectrum disorders. The current review seeks to understand how disruption of AMPA receptor (AMPAr) mediated neurotransmission in the cerebro-cerebellar circuit, particularly in genetic autism related to SHANK3 or SYNGAP1 protein dysfunction function and autism associated with in utero exposure to the anti-seizure medications valproic acid and topiramate, may contribute to the disease presentation. Initially, a discussion contextualizing AMPAr signaling in the cerebro-cerebellar circuitry and microstructural circuit considerations is offered. Subsequently, detailed review of the literature implicating mutations or deletions of SHANK3 and SYNGAP1 in disrupted AMPAr signaling reveals how bidirectional pathogenic modulation of this key circuit may contribute to autism. Finally, how pharmacologic exposure may interact with this pathway, via increased risk of autism diagnosis with valproic acid and topiramate exposure and potential treatment of autism using AMPAr modulator perampanel, is discussed. Finally, through the lens of the review, we will offer speculation on how neuromodulation may be used as a rational adjunct to therapy. Together, the present review seeks to synthesize the disparate considerations of circuit understanding, genetic etiology, and pharmacologic modulation to understand mechanistic interaction of this important and complex disorder.